Influence of hypothyroidism on renal function of lithium-treated patients - Lozano R (Dove Medical Press, 2015)
Roberto Lozano, Reyes Marín, María-Jesús Santacruz Pharmacy Department, Aragones Health Service, Zaragoza, SpainSeveral studies have shown that lithium maintenance treatment for bipolar disorder (BD) is associated with chronic kidney disease (CKD).1–3 Three recent and large controlled studies concluded that lithium treatment, within recommended serum levels, may increase the risk of induced end-stage renal disease by twofold1,2 or, alternatively, CKD is associated with BD independent of drug treatment.3 Moreover, review of the safety data on lithium shows a 0–5 mL/min reduction in glomerular filtration rate and a clear reduction in urinary concentrating capacity, during an observation period of 1 year.4